Mobile applications for nurses in the care of elderly people after a stroke: Scope review (Revista Contexto & Saúde, 2025)
Objective: to map the available scientific evidence on mobile applications to assist nurses in caring for elderly people after a stroke. Method: This is a scoping review, conducted in accordance with JBI recommendations, where searches were conducted from December 2023 to April 2024 in the listed information sources. The eligibility criteria adopted were: studies on mobile applications to assist nurses as intervention technology, guidance, rehabilitation, or other forms of care for elderly people after stroke. The selection and screening of studies were based on the use of the EndNote web reference manager and Rayyan software. Regarding the analysis of evidence, a data extraction tool developed for the review was used, which was organized in a Microsoft Excel spreadsheet. Results: a total of 346 studies were identified, and only five were selected for the final sample of the review. The results were grouped into five categories: nursing care in the functional rehabilitation of elderly people after stroke; control and self-monitoring of hypertension in elderly people after stroke; benefits of the mobile application for self-management of nursing care for elderly people in the post-stroke phase; and a mobile application for evaluating the effectiveness of care provided by nurses. Conclusion: The findings clarified that the content included in mobile applications to support nursing care was mainly associated with the rehabilitation of elderly people's functionality.
Keywords: Stroke; Mobile Applications; Nurses; Nursing care; Aged